Clinical importance of the posterior meningeal artery: a review of the literature - Wang, Guangming (Neuroradiol J, 2019)
The posterior meningeal artery, which arises from the vertebral artery, is a critical artery in neurological lesions. However, a comprehensive review of the importance of the posterior meningeal artery is currently lacking. In this study, we used the PubMed database to perform a review of the literature on the posterior meningeal artery to increase our understanding of its role in vascular lesions. The posterior meningeal artery provides the main blood supply to the paramedial and medial portions of the dura covering the cerebellar convexity. The posterior meningeal artery is often involved in dural arteriovenous fistulas occurring near the posterior fossa, and the posterior meningeal artery can be the path for transarterial embolisation or a path through which to monitor the degree of dural arteriovenous fistula embolisation. In posterior circulation ischaemia and moyamoya disease, the posterior meningeal artery can form transdural anastomoses with pial arteries at the surface of the brain, and these can help prevent ischemia. The posterior meningeal artery can also develop aneurysms, most of which are traumatic pseudoaneurysms; patients should therefore be treated in a timely manner or followed up carefully in cases of rebleeding. In addition, during a craniotomy, the posterior meningeal artery should be protected intraoperatively to avoid damaging any transdural anastomosis that may be present. In addition, when the posterior meningeal artery is the main feeding artery of an intracranial tumour, that artery is a satisfactory path for preoperative embolisation. Briefly, the posterior meningeal artery is a very important artery in neurosurgery.